First report of entomopathogenic fungi from South Sumatra (Indonesia): pathogenicity to egg, larvae, and adult of Culex quinquefasciatus - INDRI RAMAYANTI; SITI HERLINDA; AHMAD MUSLIM; HAMZAH HASYIM (Society for Indonesian Biodiversity, 2022)
Abstract. Ramayanti I, Herlinda S, Muslim A, Hasyim H. 2022. First report of entomopathogenic fungi from South Sumatra (Indonesia): pathogenicity to egg, larvae, and adult of Culex quinquefasciatus. Biodiversitas 23: 5695-5702. Mosquito control has currently used many biocontrol agents, such as entomopathogenic fungi. So, the study aimed to determine the pathogenicity of the entomopathogenic fungi from South Sumatra to the eggs, larvae, and adults of Culex quinquefasciatus. The fungal isolates used were eight isolates from South Sumatra and have been identified molecularly. The fungal species that were the most pathogenic to the eggs of Cx. quinquefasciatus were Beauveria bassiana (BSwTd4, TaLmME, TaPsBA isolates), Metarhizium anisopliae (MSwTp3 isolate), Penicillium citrinum (BKbTp isolate), and Talaromyces diversus (MSwTp1 isolate). The Cx. quinquefasciatus eggs infected with the fungus not only could kill the eggs but also could continue to kill the emerging larvae, pupae, and adult. This is the first record that B. bassiana, M. anisopliae, P. citrinum, and T. diversus from South Sumatera Indonesia were pathogenic to the eggs of Cx. quinquefasciatus and had ovicidal activity. The most pathogenic fungal species to the larvae of Cx. quinquefasciatus were M. anisopliae (MSwTp3 isolate) and B. bassiana (BSwTd4 and TaLmME isolates). Three species of entomopathogenic fungi that were the most pathogenic to the adults of Cx. quinquefasciatus were M. anisopliae (MSwTp3 isolate), B. bassiana (BSwTd4 and TaLmME isolates), and P. citrinum (BKbTp isolate). Finally, The entomopathogenic fungi from South Sumatra have the negative effect on Cx. quinquefasciatus growth. The entomopathogenic fungi from South Sumatra have potential to be developed as the ovicide, larvicide, and adulticide. The future application of the fungi against the mosquito eggs, larvae, and adults can be used an ovitrap, fungal spores formulated in a synthetic oil, and fungus-impregnated black cloths, respectively.